GE_GERICHTE C/1599/2012 vom 24. Mai 2013 - GE Cour de justice (2013)
PROTECTION DE L'UNION CONJUGALE; DROIT DE GARDE; VISITE ; LOGEMENT DE LA FAMILLE; OBLIGATION D'ENTRETIEN | CC.176; CC.163; CC.285; CC.273; CC.274.L; CC.307; CC.308